Pengaruh Internal Terhadap Pendapatan Usaha Kecil Menengah (Studi Kasus Makanan Dan Minuman Ringan Di Kecamatan Banjarmasin Utara, Kota Banjarmasin) - Muhammad Mirza Baihaqi; R Rusdiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
The income of small and medium enterprises can be influenced by various factors, both internal and external factors. In this study, internal factors such as capital, labor and working hours were used as variables. This study aims to determine the effect of the variables of capital, labor and working hours on the income of small and medium enterprises (case study of soft drinks and food in North Banjarmasin District, Banjarmasin City).The data source used in this research is primary data in the form of interviews with a sample of 45 respondents. The analytical tool used is multiple linear regression with income as the dependent variable and three independent variables, namely capital (IDR), labor (people) and working hours (hours). Multiple linear regression will test the effect simultaneously (f test) and partially (t test) through the eviws10 software.            The results of this study indicate that capital, labor, and working hours individually (partially) and collectively (simultaneously) have a significant and positive effect on the income of small and medium enterprises  (case study of soft drinks and food in North Banjarmasin District, Banjarmasin City). Meanwhile, the most dominant factor affecting the income of small and medium enterprises is capital.            Based on the results of the research, the conclusions that can be applied in order to increase income are by managing the best possible capital regularly so that the production process to marketing can run properly, then employing workers according to the needs of business activities.and carry out operational working hours in accordance with the business activities being carried out.